Building code of the Philippines : adopting a national building code of the Philippines thereby revising republic act numbered sixty-five hundred forty one. (Manila, Philippines : A. V. B. Printing Press, 2010)
Adopting a national building code of the Philippines thereby revising republic act numbered sixty-five hundred forty one.
Chapter 1 : General provisions -- Chapter 2 : Administration and enforcement -- Chapter 3 : Permits and inspection -- Chapter 4 : Types of construction -- Chapter 5 : Requirements for fire zones -- Chapter 6 : Fire-resistive requirements in construction -- Chapter 7 : Classification and general requirements of all buildings by use or occupancy -- Chapter 8 : Light and ventilation -- Chapter 9 : Sanitation -- Chapter 10 : Building projection over public street -- Chapter 11 : Protection of pedestrians during construction or demolition -- Chapter 12 : General design and construction requirements -- Chapter 13 : Electrical and mechanical regulations -- Chapter 14 : Photographic and x-ray films -- Chapter 15 : Pre-fabricated construction -- Chapter 16 : Plastics -- Chapter 17 : Sheet metal paint spray booths -- Chapter 18 : Glass and glazing -- Chapter 19 : The Use of computers -- Chapter 20 : Signs -- Chapter 21 : Transitory and final provisions
Keywords: BUILDING LAWS